Elastic symmetry and parameters of the azimuthal anisotropy of seismic waves in sedimentary strata based on vertical seismic profiling data - Prodayvoda, G.T.; Kuzmenko, P.M.; Vyzhva, A. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
The symmetry and the complete component set of a tensor matrix of elastic constants and elastic compliances are first determined by the inversion of radial velocity indicatrices for quasilongitudinal, "quick", and "slow" quasitransverse waves that are obtained according to the VSP method in the standard acoustic coordinate system. It is established that the elastic constants of clay strata have planar triclinic symmetry, and carbonate strata have axial rhombic symmetry. The value of elastic anisotropy integral coefficient is nearly 22%. The longitudinal axes and the acoustic normals of sedimentary strata are first determined according to field seismic surveys. The estimation of the approximation errors of the elastic symmetry for sedimentary strata by models with transversely isotropic and orthorhombic symmetries are calculated. It is proved that such approximation significantly changes the nature of the seismic wave azimuthal anisotropy and causes high errors, which can significantly reduce the 3D seismic efficiency in the oil and gas exploration under complex geological conditions.